Interpretation of Lineament and Shallow Structure in Gunung Batu - Lembang Area Based on 2D Resistivity Method - Junursyah, G.M. Lucki; Rokhis, Tria Ainur; Praromadani, Zulimatul Safa'ah; Sugiarto, Bambang (Badan Geologi, 2023)
The movement of Lembang fault is interpreted as active until nowadays. The fault creates a unique and beautiful geomorphology and significantly explored and developed as natural tourism destination, one of the areas is located in Gunung Batu. The research location is in the west area of Gunung Batu as a part of the Lembang fault segment. For that reason, geophysics research with 2D and 4D resistivity method is required to interpret the subsurface geological indication that related with the potency of resource and disaster. The result of interpretation method to 71 meters depth shows five layers of rock with Andesite intrusion rocks as a basement. There is an indication of weakness zone that related to the formation of reverse and normal fault as a result of the development system of Lembang fault where the area is 358.6 m2 - 1257 m2 at 19.7 m–30 m depth. Additionally, indication of groundwater aquifer is located in fined-grained permeable layer at 15.6 m - 21.1 m depth.